Implementasi Karakter Religius dan Toleransi Siswa Kelas V SD Negeri 71 Kota Bengkulu - Kurniani, Silvia; Parmadie, Bambang; Supriatna, Irfan (JURIDIKDAS, 2024)
This study aims to describe the implementation religious character and tolerance of fifth grade students at SD Negeri 71 Kota Bengkulu. This research is a qualitative research. The subjects in this study were fifth grade students and Islamic Religious Education teachers and fifth grade teachers. Data collection techniques used observation, interviews and documentation with triangulation of sources and techniques. The results of the study (1) implementation character of the religious is students there are still some students who do not participate in praying activities before and after learning, praying congregation, dressing politely and covering the genitals and doing infaq well and according to school regulations (2) implementation character of tolerance students respect and respecting other students as a form of maintaining the rights of different religions to carry out religious teachings, respecting different opinions as something human and collaborating with friends of different religions, races and ethnicities. Implementation religious character of the role, parents and teachers as educators, mentors and support for improving facilities and infrastructure in schools. The purpose of implementing the character of student tolerance is that students are able to respect every difference in religious, ethnic, racial, and cultural life.